2020
DOI: 10.1016/j.adolescence.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance and well‐being of native and immigrant students. Comparative analysis based on PISA 2018

Abstract: Introduction The emotional, cultural, and economic changes involved in the process of coping with migration can be particularly difficult during adolescence. How education systems respond to the challenges posed by the flow of immigration has profound implications for society. One of the ways that students can demonstrate their adaptation to the education system is by their academic performance. In addition, in many education systems well‐being has been shown to be directly related to performance. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 90 publications
4
12
0
2
Order By: Relevance
“…Empirical research so far has focused on differences in levels rather than on the development of life satisfaction between children of immigrants and nonimmigrants. Results are inconsistent; Some research found children of immigrants to have lower levels of life satisfaction (Stevens et al, 2015 ), whereas others found no significant differences (Rodríguez et al, 2020 ), or found children of immigrants to have higher life satisfaction (Tang, 2019 ). Since these studies measured life satisfaction at one point in time, these inconsistencies may indeed indicate differential development for children of immigrants and nonimmigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research so far has focused on differences in levels rather than on the development of life satisfaction between children of immigrants and nonimmigrants. Results are inconsistent; Some research found children of immigrants to have lower levels of life satisfaction (Stevens et al, 2015 ), whereas others found no significant differences (Rodríguez et al, 2020 ), or found children of immigrants to have higher life satisfaction (Tang, 2019 ). Since these studies measured life satisfaction at one point in time, these inconsistencies may indeed indicate differential development for children of immigrants and nonimmigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows a variation in rates of academic achievement among immigrant students and children of immigrants [33,34]. For example, Rodríguez et al [35] found that native students performed better in science and mathematics. However, De Feyter et al [36] revealed that children of immigrants showed better attendance, higher grades, and higher scores on standardized reading and math tests in comparison to their peers from native families.…”
Section: Academic Achievement For Immigrant Studentsmentioning
confidence: 99%
“…Contrasting findings seem to be explained by differences in the host country considered and what aspect of wellbeing is the focus of the study. For example, studies exploring academic and wellbeing outcomes have found that native students have better academic performance, but higher (Wang, 2021 ) or lower (Rodríguez et al, 2020 ) scores in positive affect, as well as equal (Alivernini et al, 2020 ; Rodríguez et al, 2020 ) or slightly lower (Wang, 2021 ) scores in LS. Where immigrant adolescents report lower wellbeing, differences are often explained by socio-economic characteristics, as well as friendships and loneliness, discrimination, religiosity, social participation, acculturation, and school related factors (e.g., language, bullying, school-related anxiety, fear of failure, grade repetition, etc.)…”
Section: Introductionmentioning
confidence: 99%